Primary Intestinal Fibrosarcoma in Cats - Cid, Gabriela de Carvalho; Palha de Brito Jardim, Mariana; Fernandes, Maria Eduarda dos Santos Lopes; Alves de Lima Moraes Bastos, Priscila; Santos, Carla Regina Gomes Rodrigues; Silva, Monique Lorenço e; Nogueira, Vivian de Assunção; Souza, Heloisa Justen Moreira (Acta Scientiae Veterinariae, 2022)
Background: Fibrosarcomas are malignant neoplasms of mesenchymal origin and can have different symptoms depending on the species, age, location and etiopathogenesis. Intestinal tumors in domestic cats are common and the small intestine is the most common site; however, fibrosarcomas are rare in the intestine of all animal species. This work reports intestinal fibrosarcoma in 2 domestic cats and aims to clarify and present information concerning this neoplastic type in the gastrointestinal tract of this species. Cases: We report 2 cases of intestinal fibrosarcoma in domestic felines (Felis catus). Cat 1. A 14-year-old female Persian breed, domestic cat, was taken to the Feline Sector of the Veterinary Hospital of Small Animals (HVPA) of the Federal Rural University of Rio de Janeiro (UFRRJ). The main complaint was chronic constipation and rectal prolapse. The clinical examination revealed an ulcerated mass, measuring 4.0 cm x 1.7 cm. Cat 2. A 10-year-old female undefined breed, domestic cat, was taken to the private clinic. The main complaint was diarrhea with bloody and rectal prolapse. The clinical examination revealed nodule measuring 2.5 cm in diameter. The surgical option decided upon was to use the rectal pull-through technique in both animals. The patients had no trans-surgical or postoperative complications. The material collected during the surgical interventions was analyzed macroscopically and fixed in 10% buffered formalin for 24 h and then sent to the Histopathology Laboratory of the Pathological Anatomy Sector (SAP) at UFRRJ for the cat 1 and in private laboratory for the cat 2. After fixation, it was cleaved for routine microscope exam using Hematoxylin and Eosin (HE) stains and for the histochemical method of Masson’s Trichrome staining technique. Complementary immunohistochemistry tests and electron microscopy were also performed. The patients were followed up clinically, showing complete remission of the clinical signs and survival for approximately 1 year after the neoplastic resection. Discussion: There are few reports of intestinal fibrosarcomas in veterinary medicine, therefore, little is known about racial predilection, age, sex or biological behavior. As far as these authors know, this is the 6th and 7th report of this neoplasm with a primary site in the large intestine in this species. The morphological diagnosis of fibrosarcoma is relatively simple, whereas, in some cases the differential diagnosis for tumors of the peripheral nerve sheath, leiomyosarcomas and gastrointestinal stromal tumor (GIST) can be extremely difficult. The immunohistochemistry technique in these cases may not be particularly useful. The fibrosarcoma diagnosis was also confirmed by electron microscopy since no evidence was found that could lead to a neuronal origin, thus excluding tumors such as neurofibrosarcoma and schawnoma, corroborating the immunohistochemical examination. The surgical management of tumor resection with wide safety margins (minimum 2 cm) remains the “gold standard” therapy for dealing with fibrosarcomas since they have a low response rate to chemotherapy and radiotherapy and the use of these therapies as an adjuvant is controversial. The advantages of this technique are related to the surgical time, simplicity, easy access and reduction in the risk of abdominal contamination. Histopathological, immunohistochemistry and electron microscopy evaluations were sufficient to enable the diagnosis of an intestinal fibrosarcoma in both cats. The occurrence of this neoplasm with intestinal involvement in the feline species is rare; therefore, this description is important as it provides information about epidemiology, associated signs, differential diagnoses, biological behavior, treatment and prognosis. Keywords: feline, intestine, mesenchymal, tumors, neoplasm, rectal pull-through.